2021
DOI: 10.1097/as9.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Pan-immune-inflammation Value and Prognosis in Patients With Esophageal Cancer

Abstract: The pan-immune-inflammation value was associated with clinical outcomes and tumor-infiltrating lymphocytes in 866 esophageal cancers. Systemic immune competence may influence patient prognosis through local immune response. Objective: To examine the relationship between the pan-immune-inflammation value (PIV), tumor immunity, and clinical outcomes in 866 patients with esophageal cancer. Background: The PIV, calculated from all immune-inflammatory cells in the peripheral blood count, is a recently proposed mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Fifteen studies encompassing 4942 patients were included in the meta-analyses [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The available studies were conducted on several tumors, including CRC, melanoma, breast cancer, and non-small cell lung cancer ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies encompassing 4942 patients were included in the meta-analyses [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The available studies were conducted on several tumors, including CRC, melanoma, breast cancer, and non-small cell lung cancer ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated both patients treated with immunotherapy (nivolumab and pembrolizumab alone) and targeted therapy with BRAF inhibitors/MEK inhibitors, and separate data for these treatment types were included in the subgroup analyses [ 32 ]. Ten studies included Caucasian patients [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 48 ], while five studies were conducted in the Far East [ 44 , 45 , 46 , 47 , 49 ]. Most studies had a low risk of bias according to the NOS ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a different approach, limited research has shown that blood-borne platelets, monocytes, neutrophils, and lymphocytes, which are ubiquitous in the highly inflamed GBM microenvironment, have high prognostic usefulness either alone or in distinct unique blends [31]. Constructing sound grounds for our current research, despite the facts conclusively confirming its prognostic competence in various extracranial malignancies [19][20][21][22][23][24][25][26][27][28], the unique PIV has never been examined for its prognostic potential in GBM patients. In this respect, the present research represents the first effort to investigate the prognostic strength of novel PIV in newly diagnosed GBM patients who underwent the standard Stupp regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The pan-immuneinflammatory value (PIV) is a newly created immune inflammation measure that is a unique combination of monocyte, platelet, neutrophil, and lymphocyte counts [19]. In previous reports, PIV showed a strong association with OS in patients with advanced colorectal cancer, advanced breast cancer, esophageal cancer, small-cell and non-small cell lung cancers, and Merkel cell carcinoma who underwent surgery and/or systemic therapy [19][20][21][22][23][24][25][26][27][28]. Gliomas, particularly GBM, have a severe inflammatory and immunosuppressive milieu that permits them to evade the antitumor immune response, evidencing that the novel PIV might be employed as a likely predictor of outcomes in such patients [9].…”
Section: Introductionmentioning
confidence: 99%